ANALYSIS OF THE PROFITABILITY OF MERANG MUSHROOM FARMING IN BAKTIYA BARAT DISTRICT, NORTH ACEH DISTRICT - Nisaul Husna; Jamilah; Muhammad Authar; Riani (PT. Radja Intercontinental Publishing, 2023)
This study uses a quantitative descriptive method. From the calculation of the profitability studied, it shows that the mushroom farming has the ability and obtains a profit or profitability of 50%. This shows that the mushroom farming gets a large profit from the production activities that are cultivated. Based on the results of research and analysis of the profitability of the data that has been carried out on the mushroom farming of Mr. Tarmizi in Baktiya Barat District, North Aceh Regency, it can be concluded, among others: 1. The total costs incurred on the mushroom farming for one production process are Rp. 3,571,478.9 with details of fixed costs of Rp. 225,478.9 and variable costs of Rp. 3,346,000. With the income obtained is Rp. 7,500,000 so that's a profit of Rp. 3,928,521.1. 2. Straw mushroom farming is a farm engaged in agriculture that is able to earn a profit of 50%.